2012
DOI: 10.1016/j.parkreldis.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes induced by theta burst stimulation of the cerebellum in dyskinetic Parkinson’s disease patients

Abstract: a b s t r a c tBackground: Cerebellar repetitive transcranial magnetic stimulation may be effective in reducing peakdose levodopa induced dyskinesia in Parkinson's disease patients. It was proposed that the antidyskinetic effect could be due to modulation of cerebello-thalamo-cortical pathways. However the neural basis for these clinical effects have not yet been demonstrated. Methods: We investigated the effects of repeated sessions of cerebellar continuous theta burst stimulation in Parkinson's disease patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…Other authors have proposed that the cerebellum is itself an important site of maladaptive plasticity in both PD and LID. According to this view, increased cerebellar activity would be a compensatory response to an altered processing of movement-related information in striato-thalamo-cortical circuits, and robust plastic responses in the cerebellum would increase the likelihood to develop LID (Brusa et al 2012; Koch et al 2009). …”
Section: Role Of the Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have proposed that the cerebellum is itself an important site of maladaptive plasticity in both PD and LID. According to this view, increased cerebellar activity would be a compensatory response to an altered processing of movement-related information in striato-thalamo-cortical circuits, and robust plastic responses in the cerebellum would increase the likelihood to develop LID (Brusa et al 2012; Koch et al 2009). …”
Section: Role Of the Cerebellummentioning
confidence: 99%
“…There is circumstantial evidence of increased cerebellar compensation in LID, as suggested by finding of increased metabolic activity in the deep cerebellar nuclei (Brusa et al 2012) and in the red nucleus (Lewis et al 2013), which is an important projection target of the deep cerebellar nuclei.…”
Section: Role Of the Cerebellummentioning
confidence: 99%
“…Investigations aimed at modelling the DCS electric field in humans demonstrated that maximal activation was localised to the targeted cerebellar hemisphere [54]. In contrast, repetitive TMS protocols in Parkinson's disease patients were found to alter metabolic activity in both cerebellar cortex and the deep cerebellar nuclei [55]. Similarly, cerebellar DCS does not alter the excitability of M1 to single pulse TMS, while cerebellar repetitive TMS increased the MEP response [56].…”
Section: Non-invasive Cerebellar Stimulationmentioning
confidence: 99%
“…In patients with PD, with mild to moderate LID, repeated sessions of bilateral cerebellar inhibitory stimulation after regular doses of levodopa induce a sustained reduction of dyskinesia lasting at least 2 weeks (30, 129). Repeated cerebellar stimulation can also reduce the cerebellar cortical activity and enhance dentate nuclear activity in imaging studies in PD patients with dyskinesias (130). In such patients, a single session of inhibitory stimulation of the cerebellar cortex combined with levodopa can restore the sensorimotor plasticity tested by PAS, but not the local intracortical plasticity as tested with TBS (30).…”
Section: Cerebellar Link To Motor Circuits In Health Parkinsonism Anmentioning
confidence: 99%